Interrelation of dams sustainability with the local communities and water quality - A. Al-Afeshat; M.M. Zoubi; Q.Y. Abu Afifeh; H. Al-Jawaldeh; T.A. Qutishat; A.M.N. Masoud; M. Rahbeh (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Dams are vital for water management but significantly impact local communities. Balancing development with sustainability requires understanding these effects. The study aims to explore the complex interconnection between dam sustainability, water quality chemistry, and local communities.METHODS: The environmental pillar for Jordanian dams was shaped by climate conditions and seismic activity, while the socioeconomic factors involved intersections density, population growth, and unemployment in the areas surrounding the dams, all of which significantly influence dam sustainability. The Wroclaw Taxonomic Method was used to develop the Index of Sustainable Dams, while the Granger Causality Test assessed causal connections among sustainability pillars.FINDINGS: The study classified dams performance using the Index of Sustainable Dams values. High-performance dams, with values from 0.010 to 0.299, included Kafrein, King Talal, and Wadi Shu'eib dams. Moderate performance, ranging from 0.299 to 0.528, comprised only Kufranja dam. Low-performance dams, with values from 0.528 to 0.937, included Wala, Wadi Arab, Zarqa-Main, and Mujib dams. Moreover, the findings reveal that the dams were significantly influenced by chemical factors (electrical conductivity and the biological oxygen demand to chemical oxygen demand ratio). An average electrical conductivity of 1116 microsiemens per centimeter negatively affects dam sustainability and community engagement, highlighting water salinity's detrimental impact. Conversely, a biological oxygen demand to chemical oxygen demand ratio of 0.09 positively influences sustainability and agricultural productivity, suggesting more efficient organic matter processing in well-functioning systems. Additionally, 8.6 percent of agricultural employment and 1.4 percent of female participation play crucial roles in shaping dams sustainability.CONCLUSION: Strong bidirectional causal relationships were observed between dams sustainability and changes in employment opportunities in the agricultural sector. Dam managers can use the index for Jordanian dams to pinpoint weaknesses, prioritize improvements, and track progress for enhanced sustainability.